Keragaman Jenis Paku-Pakuan (Pteridophyta) dan Kajian Potensi Pemanfaatannya di Cagar Alam Ulolanang Kecubung - Muhammad A'tourrohman Atho; M. Akmal Surur Akmal; Riza Eka Nabila Riza; Sinta Dewi Rahmawati Sinta; Siti Fatimah Fatim; Dian Naili Ma'rifah Dian; Lianah Lianah (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Cagar Alam Ulolanang Kecubung as a conservation area in Batang, Central Java undoubtedly holds a rich diversity of flora and fauna. One of the flora stored in the CA is ferns. Ferns (Pteridophyta) is one of the germplasm that plays an important role in the forest ecosystem and is useful in human life. Spread of fern is very wide in the territory of Indonesia. Ferns have a variety of types and potential for extraordinary use for feed ingredients, medicine and ornamental plants. This research is to obtain data and information about the types of ferns diversity in the CA Ulolanang Potential resources, especially from the community around the area. This research was conducted in March-April 2020 using the method of literature study from books, national and international journal articles. Data obtained, there are 15 types of plants distributed namely Davalia trichomanoides Bedd., Davalia denticulata (Brumm.) Mett., Pyrrosia lingua Farw., Pyrrosia numularifolia Sw., Pyrrosia longifolia (Burm.f.) Morton, Drynaria quersifolia (L.) Smith., Drynaria sparsisora